Optimizing the beam-like structure of a vehicle body using the grey–fuzzy–Taguchi method. Issue 1 (2nd January 2021) - Yao, Weimin; Cai, Kefang; Xu, Yangwei
Abstract : The static–dynamic performance of body-in-prime (BIP) which contains glass was improved by optimizing its beam-like structure parameters. An implicit parametric model of BIP was built using SFE CONCEPT TM, which is verified by a physical test. An L 32 (4 8 ) orthogonal array was applied to perform the design of experiments analysis. A hybrid method of the Taguchi technique, grey relational analysis and fuzzy logic was employed to determine the optimal combination of design parameters to improve the static-dynamic performance of BIP without considerably increasing weight. The grey–fuzzy–Taguchi and grey–Taguchi methods were compared to illustrate the advantage of the former method in improving the uncertainty of response parameters. Optimization results indicated that bending stiffness, torsion stiffness, first order bending natural frequency and first torsion natural frequency were improved by 16.70%, 10.13%, 5.57% and 5.95%, respectively, with 1.48% increase in BIP weight by using the proposed method.